Acquisition of negative complement regulators by the saprophyte Leptospira biflexa expressing LigA or LigB confers enhanced survival in human serum - Castiblanco-Valencia, Mónica M. (Immunol Lett, 2016)
Leptospiral immunoglobulin-like (Lig) proteins are surface exposed molecules present in pathogenic but not in saprophytic Leptospira species. We have previously shown that Lig proteins interact with the soluble complement regulators Factor H (FH), FH like-1 (FHL-1), FH related-1 (FHR-1) and C4b Binding Protein (C4BP). In this study, we used the saprophyte L. biflexa serovar Patoc as a surrogate host to address the specific role of LigA and LigB proteins in leptospiral complement evasion. L. biflexa expressing LigA or LigB was able to acquire FH and C4BP. Bound complement regulators retained their cofactor activities of FI in the proteolytic cleavage of C3b and C4b. Moreover, heterologous expression of ligA and ligB genes in the saprophyte L. biflexa enhanced bacterial survival in human serum. Complement deposition on lig-transformed L. biflexa was assessed by flow cytometry analysis. With regard to MAC deposition, L. biflexa expressing LigA or LigB presented an intermediate profile: MAC deposition levels were greater than those found in the pathogenic L. interrogans, but lower than those observed for L. biflexa wildtype. In conclusion, Lig proteins contribute to in vitro control of complement activation on the leptospiral surface, promoting an increased bacterial survival in human serum.